Efektifitas Berbagai Zat Pengatur Tumbuh (ZPT) Alami Pada Pertumbuhan Tanaman Seledri (Apium graveolens L.) - Karima Nur Maulida; R Budiasih; Lia Sugiarti (Fakultas Pertanian Universitas Winaya Mukti, 2021)
The experiment was carried out in Ciumbuleuit, Hegarmanah Sub-district, Cidadap District, Bandung City, with an altitude of 875 meters above sea level with the Andosol order. The time of the experiment was started from June - August 2020. The purpose of this study was to study and analyze the effectiveness of the best natural growth regulators (ZPT) on the growth of celery (Apium graveolens L.). The experimental design used was a simple randomized block design (RBD) with four treatments and repeated six times. The treatments were A = 100% water (control), B = 30% shallot extract, C = 30% bean sprout extract, and D = 30% coconut water. The results showed that different natural ZPT administration had an effect on the growth of celery plants. And the experimental results based on independent tests showed that giving D treatment, coconut water at a concentration of 30% affected the growth of plant height 21 DAS, number of leaves 35 DAS and 42 DAS, leaf length 35 DAS and 42 DAS and the number of tillers 42 DAS on celery plants compared other treatment.